Characteristics of gap regeneration in mangrove forests of Dong Rui, Tien Yen, Quang Ninh - Hanh, Nguyen Hoang; Tuan, Mai Sy; Tinh, Pham Hong; Hanh, Nguyen Thi Hong (Academia Journal of Biology, 2018)
Field surveys using unmanned aerial vehicle monitoring were conducted in combination with satellite image analysis to evaluate the characteristics of gaps inside mangrove forest vegetation in Dong Rui commune, Tien Yen district, Quang Ninh province as well as the natural regeneration inside these gaps. A total of 15 gaps was located in four survey plots totaling 22,500 m2, among which four different types of mangrove forest communities were found, being dominated by (1) Bruguiera gymnorrhiza; (2) Aegriceras corniculatum, Kandelia obovata, Rhizophora stylosa and Bruguiera gymnorrhiza; (3) Bruguiera gymnorrhiza, Rhizophora stylosa; and (4): Aegriceras corniculatum, Kandelia obovata, respectively. Based on observations from 2012 to 2018, changes in regenerated tree densities were similar between gaps with a poor diversity of 2–5 species resembling the composition of the surrounding canopy. In some gaps, species not found in the nearby vegetation were observed with lower densities. Thus, the regeneration and patching of the mangrove forest gaps in Dong Rui were quite uniform at a midium rate. Species composition inside gaps did not differ significantly from the surrounding magrove forest communities. However, the ecological dominance of each species varied over time, depending on several natural factors and human actitvities where gaps were formed